2017
DOI: 10.1097/rlu.0000000000001706
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer Diagnosed by Thyroid Scintigraphy

Abstract: We report a 34-year-old man referred because of increasing dysphagia secondary to goiter. Thyroid scintigraphy and SPECT/CT images helped to recognize an unsuspected esophageal dilation due to a poorly differentiated adenocarcinoma arising at the lower end of the esophagus. Further examinations are mandatory when abnormal activities are observed during thyroid scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The activity on 99m TcO 4 − imaging in tumor had to be taken into consideration. Calvo-Morón et al 7 reported nonspecific accumulation of 99m TcO 4 − in endoesophageal, which was pathologically confirmed as poorly differentiated adenocarcinoma of esophageal mucosa. Similarly, intense 99m TcO 4 − activity in parathyroid carcinoma was also reported before 8 .…”
mentioning
confidence: 96%
“…The activity on 99m TcO 4 − imaging in tumor had to be taken into consideration. Calvo-Morón et al 7 reported nonspecific accumulation of 99m TcO 4 − in endoesophageal, which was pathologically confirmed as poorly differentiated adenocarcinoma of esophageal mucosa. Similarly, intense 99m TcO 4 − activity in parathyroid carcinoma was also reported before 8 .…”
mentioning
confidence: 96%